Repeated inoculation with rumen fluid accelerates the rumen bacterial transition with no benefit on production performance in postpartum Holstein dairy cows - Fanlin Kong; Feiran Wang; Yijia Zhang; Shuo Wang; Wei Wang; Shengli Li (Journal of Animal Science and Biotechnology, 2024)
Abstract Background The dairy cow’s postpartum period is characterized by dramatic physiological changes, therefore imposing severe challenges on the animal for maintaining health and milk output. The dynamics of the ruminal microbiota are also tremendous and may play a crucial role in lactation launch. We aim to investigate the potential benefits of early microbial intervention by fresh rumen microbiota transplantation (RMT) and sterile RMT in postpartum dairy cows. Twelve fistulated peak-lactation dairy cows were selected to be the donors for rumen fluid collection. Thirty postpartum cows were divided into 3 groups as the transplantation receptors respectively receiving 10 L fresh rumen fluid (FR), 10 L sterile rumen fluid (SR), or 10 L saline (CON) during 3 d after calving. Results Production performance, plasma indices, plasma lipidome, ruminal microbiome, and liver transcriptome were recorded. After fresh and sterile RMT, we found that the molar proportion of propionic acid was increased on d 7 in the FR and SR groups and the bacterial composition was also significantly changed when compared with the CON group. A similarity analysis showed that the similarities between the CON group and FR or SR group on d 7 were 48.40% or 47.85%, whereas the similarities between microbiota on d 7 and 21 in the FR and SR groups were 68.34% or 66.85%. Dry matter intake and feed efficiency were not affected by treatments. Plasma β-hydroxybutyrate concentration in the FR group was decreased and significantly different lipids mainly included phosphatidylcholine and lysophosphatidylcholine containing polyunsaturated fatty acids. Hepatic transcriptomics analysis indicated acute-phase response pathways were upregulated in the SR group. Conclusions Our study suggests that RMT can shorten the transition process of the ruminal microbiota of postpartum dairy cows with no benefit on dry matter intake or feed efficiency. Inoculation with rumen fluid may not be a useful approach to promote the recovery of postpartum dairy cows. Graphical Abstract